Atraksi Wisata Berbasis Community Based Tourism (CBT) di Desa Wisata Kubu Gadang - Aditya Rizal Pratama; Trisna Putra (Lembaga Pengembangan Kinerja Dosen, 2023)
Ekor Lubuk Subdistrict where Kubu Gadang is located is the Subdistrict with the lowest population density in Padang Panjang City. Based on that substratum, it’s need to be researching how was the involved of the people to developing the tourism attractions with community based tourism in Kubu Gadang. Therefore, this study aims to see how tourist attractions are focused on community base cultural tourism attractions or community based tourism in Kubu Gadang Village through 5 principles of CBT. This research is descriptive research with qualitative data. as for the data collection techniques used, using the method of observation, interviews dan documentation. This study used a non-random sampling technique with a purposive sampling method involving several informants. The data obtained is reduced by summarizing, selecting and focusing on the things that are important and analyzing the data obtained on the problems studied. The result of this study indicate that there are several field applications related to tourist attractions in Kubu Gadang carried out by the Kubu Gadang village community through 5 CBT principles that sorted from the strongest namely cultural, economic, social, political and environmental principles. which show that tips are carried out by the village community Kubu Gadang tourism in developing their community based tourism attractions (CBT)